Laboratory Evaluation Of The Crown Impact On The Control Of Pier Scour Protection At A 90 Degree Bends - Ehsanbakhsh, Mojtaba; Sajadi, Seyd Mohsen; Daraie, Iman; Galeh, Heshmat Alah Mossaie (The Turkish Online Journal of Design Art and Communication, 2016)
Bridges are among the most important river structures. One the most effective factor for the destruction of bridges is the local scour around bridge piers. Every year, many bridges around the world are damaged because of not considering the role of hydraulic factors. Accordingly,for a reliable design, precise estimation of scour around bridge piers is necessary. In this study, the impact of the crown in the 90-degree bend scour at bridge pier is studied. Moreover, the bases of 2.5 cm and 5 cm in both modes, with the crown and without the crown were studied, including crowns with 2.5 cm and 5 cm and 7.5 cm diameter in a rectangular channel at an angle of 30 degrees and by measuring the water flow in three modes of 12 and 14 and 16 liters per second.The water depth in the channel for each flow was considered in the order of 8 cm and 10 cm and 12 cm that the Ds / y means the maximum depth of scour had an acceptable significance in two modes with scour and without scour and therefore, we obtained the results of processing by using two statistical software Excel and Spss that respectively are graphs and regression equation for both modes.
Keywords: pier; scour; crown